PNG agricultural cluster evaluation. (AusAID evaluation, 1998)
This report presents the findings of a post-evaluation mission during August/September 1997. Assessment is made of four completed AusAID's PNG renewable resources sector projects' sustainability, potential development impact and effectiveness in achieving their objectives. The projects selected are: Cocoa Quality Improvement Project, Keravat, East New Britain province; Coffee Research Institute Project, Aiyura, Eastern Highlands province; PNG Resource Information Sysem, Port Moresby and lae, Moreobe province; and Forestry Rapid Resource Appraisal, Port Moresby.